2015
DOI: 10.1111/jgh.12742
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic roles of carbon monoxide in intestinal ischemia‐reperfusion injury

Abstract: Intestinal ischemia-reperfusion (I-R) injury is a complex, multifactorial, pathophysiological process with high morbidity and mortality, leading to serious difficulty in treatment. The mechanisms involved in the pathogenesis of intestinal I-R injury have been examined in detail and various therapeutic approaches for intestinal I-R injury have been developed; however, existing circumstances have not yet led to a dramatic change of treatment. Carbon monoxide (CO), one of the by-products of heme degradation by he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…Carbon monoxide (CO) is endogenously produced in cells and tissues as the byproduct of heme oxygenase (HO) enzymes after heme catalytic activity [13] , [14] . Although CO is toxic to human bodies at high concentration, low-dose exogenous CO (approximately 250–500 ppm) treatment has been demonstrated to have protective functions, anti-inflammatory and antiapoptotic effects in various human diseases [15] , [16] , [17] , [18] . Furthermore, accumulating studies over the past decade have shown that low concentration of CO, or CO-releasing molecules (CORMs), can confer several molecular mechanisms, including eliminating microbes, regulating cell death and organ dysfunction, and promote immune response through resolving mediator-heme oxygenase-1 circuits [19] , activation of p38 MAPK, enhanced PPAR-γ singaling, and suppression of TLRs translocation [13] , [16] , [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Carbon monoxide (CO) is endogenously produced in cells and tissues as the byproduct of heme oxygenase (HO) enzymes after heme catalytic activity [13] , [14] . Although CO is toxic to human bodies at high concentration, low-dose exogenous CO (approximately 250–500 ppm) treatment has been demonstrated to have protective functions, anti-inflammatory and antiapoptotic effects in various human diseases [15] , [16] , [17] , [18] . Furthermore, accumulating studies over the past decade have shown that low concentration of CO, or CO-releasing molecules (CORMs), can confer several molecular mechanisms, including eliminating microbes, regulating cell death and organ dysfunction, and promote immune response through resolving mediator-heme oxygenase-1 circuits [19] , activation of p38 MAPK, enhanced PPAR-γ singaling, and suppression of TLRs translocation [13] , [16] , [20] .…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the inhalation of 2% H 2 also attenuated intestinal injuries caused by severe sepsis in male Nrf2 KO mice by regulating HO-1 and HMGB1 release [ 122 ]. Moreover, an in vivo study revealed that H 2 inhalation improved the prognosis in patients with stage IV colorectal cancer by activating PGC-1 α and restoring exhausted CD8+ T cells [ 123 ].…”
Section: Preventive and Therapeutic Applications Of H 2 mentioning
confidence: 99%
“…Many animal models have established the efficacy of hydrogen against cancers. The attributes of hydrogen include blocking of the regulator for chromosome condensation [ 43 ], some crucial molecules in stemness [ 165 ], proliferation [ 123 ], and angiogenesis [ 165 ], and the alleviation of oxidative stress. The combination therapy of hydrogen and other novel antineoplastic drugs, such as LY294002 [ 166 ], which is an inhibitor of PI3K, has demonstrated great potential and efficacy.…”
Section: Preventive and Therapeutic Applications Of H 2 mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many studies demonstrated that CO, a by-product of heme catabolism, possesses various physiological effects including anti-inflammatory, anti-apoptotic, antioxidant, and anti-proliferative property in vitro and in vivo [26,27]. Therefore, CO was applied to treat organ stress including acute myocardial injury, acute spinal cord injury [28], acute kidney injury [29], and ALI [30].…”
Section: Discussionmentioning
confidence: 99%